Lending cycles and real outcomes: Costs of political misalignment - Çağatay Bircan; Orkun Saka (Bank of Finland, Institute for Economies in Transition (BOFIT), 2019)
We use data on the universe of credit in Turkey to document a strong political lending cycle. State-owned banks systematically adjust their lending around local elections compared with private banks in the same province. There is considerable tactical redistribution: state-owned banks increase credit in politically competitive provinces which have an incumbent mayor aligned with the ruling party, but reduce it in similar provinces with an incumbent mayor from the opposition parties. This effect only exists in corporate lending as opposed to consumer loans, suggesting that tactical redistribution targets job creation to increase electoral success. Political lending influences real outcomes as credit-constrained opposition areas suffer drops in employment and firm sales. There is substantial misallocation of financial resources as credit constraints most affect provinces and industries with high initial efficiency.
URN:NBN:fi:bof-201901221040
Keywords: G21; D72; D73; P16; 330